The effect of participation education on maternal role adaptation in mothers with premature infants in the neonatal intensive care unit - Hoda Ghafari_rad; Afsaneh Arzani; Ali Zabihi; Zahra Akbarian_rad; Mojtaba Qanbari Qalehsari; Seyedeh Roghayeh Jafarian_amiri (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The birth of a premature infant, hospitalization, and separation from the family cause disruption on maternal role adaption. This study was conducted with the aim of investigating the effect of participation education on maternal role adaption in mothers of premature infants hospitalized in the neonatal intensive care unit. MATERIALS AND METHODS: This semiexperimental study was conducted with the participation of 129 eligible mothers with premature infants into three groups of 43 (face-to-face education, virtual education, and control). Data collection was done using a checklist measuring adaptation to the maternal role. Data were analyzed by descriptive statistical and multiple linear regression tests at a significance level of P < 0.05. RESULTS: The mean age of mothers was 30.8 years, the mean gestational age of infants was 31.7 weeks, the mean birth weight was 1781.4 g, and the most common (84.5%) reason for hospitalization of infants was respiratory distress. Multiple linear regression analysis showed that the total score of maternal role adaptation at the time of discharge was significantly different in the two groups of virtual education (134.362 ± 0.925) (P < 0.001) and face-to-face education (132.421 ± 0.928) (P = 0.005) with the control group (128.286 ± 0.924). CONCLUSION: The implementation of educational programs is a suitable solution to improve maternal role adaption. Therefore, it is recommended that managers and healthcare planners consider codified and regular educational programs in order to increase the ability of mothers, in order to adapt to the maternal role.